ANALISIS BUDAYA ORGANISASI DAN ASIMETRI INFORMASI DALAM SENJANGAN ANGGARAN - Ernawaty Usman; Selmita Paranoan; Sugianto Sugianto (Universitas Brawijaya, 2012)
Abstract: Analysis of Organizational Culture and Information Asymmetry Budgetary Slack. This study aims to 1) examine the influence of budget participationon budgetary slack. 2) examine the influence organizational culture as anindependent variable, pure or quasi moderation in the relationship between budgetaryparticipation with the budgetary slack. 3) examine the information asymmetry as an independent variable, pure or quasi moderation moderation in the relationship between budgetary participation with the budgetary slack. The method ofanalysis is the field of research and multiple linear regression analysis. The results showed that 1) budget participation has a positive relationship with budgetary slack. 2). organizational culture is a moderating variable and 3) Information asymmetryas quasi moderating variables. Abstrak: Analisis Budaya Organisasi dan Asimetri Informasi dalam Senjangan Anggaran. Penelitian ini bertujuan 1) menguji pengaruh partisipasi anggaran terhadap senjangan anggaran. 2) menguji budaya Organisasi sebagai variabel independen, pure moderasi atau kuasi moderasi terhadap hubunganantara partisipasi anggaran dengan senjangan anggaran. 3) menguji asimetri informasi sebagai variabel independen, pure moderasi atau kuasi moderasi terhadap hubungan antara partisipasi anggaran dengan senjangan anggaran. Metode analisis yang digunakan adalah yaitu penelitian lapangan dan analisis regresi linear berganda. Hasil penelitian menunjukkan bahwa 1) Partisipasi anggaran memiliki hubungan positif terhadap senjangan anggaran 2) Budaya organisasi merupakan variabel moderasi dan 3) Asimetri informasi sebagai variabel kuasi moderasi.